Effect of Dietary Copper on Intestinal Microbiota and Antimicrobial Resistance Profiles of Escherichia coli in Weaned Piglets - Zhang, Yiming; Zhou, Jian; Dong, Zhenglin; Li, Guanya; Wang, Jingjing; Li, Yikun; Wan, Dan; Yang, Huansheng; Yin, Yulong (Frontiers in Microbiology, 2019)
Copper is an essential microelement for animals. Pharmacological dose of copper is used as a feed additive in pig husbandry to improve growth performance, but it also has an effect on intestinal microbes and can exacerbate bacterial resistance. However, there are few reports on the effects of pharmacological dose of copper on intestinal microorganism and antimicrobial resistance profiles of pathogenic bacteria in pigs, such as E. coli. Therefore, the aim of this study was to investigate the effects of pharmacological dose of copper on the microbial communities in the hindgut and the antimicrobial resistance profiles of E. coli in weaned piglets. Twenty-four healthy weaned piglets aged 21 ± 1 days and with an average weight of 7.27 ± 0.46 kg were randomly divided into 4 groups. The control group was fed a basal diet, and treatment groups fed a basal diet supplemented with 20, 100 and 200 mg copper/kg feed in the form of CuSO4 respectively. The anal swabs were collected at the d 0, d 21 and d 42 of the trail, and the E. coli had been isolated. Meanwhile, ileum and cecum contents from the control and 200 mg copper/kg feed groups were collected at the d 21 and d 42 for microbial community analysis and E. coli isolation. All E. coli strains isolated were used for antimicrobial resistance profiles analysis. The results revealed that pharmacological dose of copper did not significantly change the diversity but significantly affected the compositions of microbial communities in both ileum and cecum contents, then affected the microbial metabolic functions in energy metabolism, protein metabolism and amino acids biosynthesis. Specifically, the copper treatments increased the richness of E. coli in hindgut, accompanied with the increased rates of E. coli resistant to chloramphenicol and ciprofloxacin. Moreover, the rate of E. coli resistant to multiple drugs increased in ileum contents of the pigs fed with pharmacological dose of copper. Thus, pharmacological dose of copper affected the compositions of microbial community, increased antimicrobial resistance rates of intestinal E. coli and was probably harmful to the health of piglets in the early stage after weaning.